Victims’ role in the criminal justice system: A statutory analysis of victims’ rights in U.S. - Boateng, Francis D. (International journal of police science & management, 2017)
In theory, crime victims have several rights and privileges—ranging from the rights to be heard to the right to confer with the prosecution. However, they are still considered as the forgotten individuals in the system because of underlying issues associated with the implementation of victims’ rights laws. Today, most states do not have any effective mechanisms of implementing legislation guaranteeing the rights of victims. The primary purpose of this article is to offer a comparative assessment of victims’ rights legislation in USA and to discuss some of the issues inherent in the implementation of these laws. Issues such as the lack of professional knowledge, the lack of enforcement mechanisms, strict eligibility criteria for compensation, varying definitions of victim across jurisdictions, and the limited scope of most crime victim legislation are discussed. The article also discusses ways to address the issues identified.